Orthodoxy, liberalism, and adaptation: essays on ways of worldmaking in times of change from biblical, historical, and systematic perspectives - Becking, Bob (Brill eBook titles, 2011)
Preliminary Material /B. E. Becking -- Introduction Why This Volume /Bob Becking -- Chapter One. Religious Orthodoxy As A Modality Of “Adaptation” /Staf Hellemans -- Chapter Two. Does An Exclusive Veneration Of God Necessarily Have To Be Violent? Israel’s Stony Way To Monotheism And Some Theological Consequences /Rainer Albertz -- Chapter Three. Coping With Violence In The Bible: A Response To Rainer Albertz /Jan Willem Van Henten -- Chapter Four. “Common Judaism”, “The Parting Of The Ways”, And “The Johannine Community” /Adele Reinhartz -- Chapter Five. Believing, Belonging, And Adapting: The Case Of Religious Modernism /Ernestine Van Der Wall -- Chapter Six. “When Creed And Morals Rot ...”: Orthodoxies Versus Liberalisms In The Nineteenth-Century Netherlands Reformed Church /David J. Bos -- Chapter Seven. Truth, Orthodoxy, And The Nouvelle Théologie: Truth As Issue In A “Second Modernist Crisis” (1946–1950) /Jürgen Mettepenningen -- Chapter Eight. Orthodoxy, History And Theology: Recontextualisation And Its Descriptive And Programmatic Features /Lieven Boeve -- Chapter Nine. Orthopraxis And Being Faithful To One’s Tradition /Peter Jonkers -- Chapter Ten. Reconstructing The Change From Judaism To Christianity As A Paradigm Shift /Dirk-Martin Grube -- Chapter Eleven. Christian Fundamentalism As A Reaction To The Enlightenment Illustrated By The Case Of Biblical Inerrancy /Marcel Sarot -- Chapter Twelve. The Ambivalence Of Adaptation And The Ongoing Strength Of Religion /Bob Becking -- Bibliography /B. E. Becking -- Index Of Texts /B. E. Becking -- Index Of Authors /B. E. Becking -- Index Of Subjects /B. E. Becking.